Asasi Newsletter: Issue No. 2 (August 2015) - Centre of, Foundation Studies (Center of Foundation Studies, 2015)
Research Bulletin Committee has managed to publish the second edition of the Asasi Newletter in such a short time. I'd like to take this opportunity to say a big 'Thank You' to those involved. I can see that our lecturers are slowly but surely immersing themselves into research as can be seen by the number of research papers and the emergence of new researchers as compared to the last newsletter. It is by no means, as easy task to do research especially so when here, in Center of Foundation Studies (CFS), we do not have our own research facilities. So, congratulation to lecturers who managed to continue to be involved with research and hopefully inspire other to do so.